2020
DOI: 10.3390/antiox9070598
|View full text |Cite
|
Sign up to set email alerts
|

MZe786 Rescues Cardiac Mitochondrial Activity in High sFlt-1 and Low HO-1 Environment

Abstract: Hypertensive disorder in pregnancy is a major cause of maternal and perinatal mortality worldwide. Women who have had preeclampsia are at three to four times higher risk in later life of developing high blood pressure and heart disease. Soluble Flt-1 (sFlt-1) is elevated in preeclampsia and may remain high postpartum in women with a history of preeclampsia. Heme oxygenase-1 (Hmox1/HO-1) exerts protective effects against oxidative stimuli and is compromised in the placenta of pregnant women with preecla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 90 publications
1
14
0
1
Order By: Relevance
“…MZe786 suppressed the increase sFlt-1 that was a likely result of decreased CSE expression in the mRUPP model. As observed in our earlier publications [ 19 ], this was probably due, in part, to the increased expression of the antioxidant genes and improved mitochondrial biogenesis that suppressed oxidative stress.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…MZe786 suppressed the increase sFlt-1 that was a likely result of decreased CSE expression in the mRUPP model. As observed in our earlier publications [ 19 ], this was probably due, in part, to the increased expression of the antioxidant genes and improved mitochondrial biogenesis that suppressed oxidative stress.…”
Section: Discussionsupporting
confidence: 75%
“…We recently reported that MZe786 rescues mitochondrial activity by stimulating cardiac mitochondrial biogenesis and antioxidant defence in heme oxygenase-1 deficient mice under high sFlt-1 environment [ 19 ]. With a good safety profile, MZe786 was a good H 2 S releasing candidate for testing in an animal model of preeclampsia [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations